KEBIASAAN CUCI TANGAN, BERJEMUR, DAN MEDIA INFORMASI PADA MASYARAKAT SUMATRA SELATAN SELAMA MASA PANDEMI COVID-19 - Yunianto, Andi Eka; Elya, Elya; Fajar Ningsih, Windi Indah; Yuliantini, Emy; Haya, Miratul; Faridi, Ahmad; Eliza, Eliza (Politeknik Kesehatan Kemenkes Bengkulu, 2020)
COVID-19 is an infectious disease caused by corona virus. This study aims to look at the habit of washing hands, sunbathing, and media information obtained by the people of southern Sumatra during the COVID-19 pandemic. This study used a cross-sectional design with 419 respondents as many as 16 years old who lived in South Sumatra Province. The questionnaire in this study was in the form of e-survey using google form media and distributed through social media (Whatsapp, Facebook, and Instagram). A Chi-square test was used to see the relationship between hand washing, sunbathing, and media information on men and women. The results showed that hand washing (OR = 1,127; 95% CI: 1,089 - 1,167) there was no significant relationship between men and women, while there was a significant relationship in sunbathing (OR = 1,884; 95% CI: 0.992 - 3,581) and information media (OR = 0.473; 95% CI: 0.246 - 0.911). The community is expected to apply the habit of washing hands, sunbathing, and digging information in various media in overcoming the prevention and impact of COVID-19.